Health risk assessment of metal(loid)s for land application of domestic sewage sludge in city of Bursa, Turkiye - Yakamercan, Elif; Aygun, Ahmet (Springer, 2023)
This study aims to determine the potential health risks (Carcinogenic and non-carcinogenic) of metal(loid)s in sewage sludge samples for agricultural purposes. For this purpose, sewage sludge was collected annually from a domestic wastewater treatment plant, and metal(loid)s were determined by ICP-MS. Metal(loid)s concentration in sludge samples was within the legal standards. No statically significant seasonal variation of metal(loid)s were observed. The total cancer risk and the hazard index (HI) of metal(loid)s through ingestion, dermal, and inhalation exposure from sewage sludge samples were estimated. The main risk contributor to metal(loid)s were Pb, Zn, and Ni. The average HI values were 0.75 (child) and 0.09 (adult). The total carcinogenic risk (TCR) for child and adult was found to be 3.43 x 10(-5) and 2.31 x 10(-5), respectively. EPA risk assessment model and Monte Carlo Simulation were used to estimate probability and sensitivity distributions for carcinogenic and non-carcinogenic risks. Sensitivity analysis showed that metal(loid)s concentration, exposure duration, exposure frequency, and body weight significantly affect total health risk. The sewage sludge can be applied safely in agriculture due to no important carcinogenic and non-carcinogenic risk for child and adult.
Keywords: Sewage sludge; Metal(loid)s; Risk assessment; Monte Carlo simulation; Sensitivity analysis